(untitled) (Pedagogy of Higher and Secondary Education, 2011)
The article reveals some theoretical grounds for the technology of forming higher pedagogical educational establishments students’ cognitive indeoendence in the process of foreign language learning. They resulted in the five steps of realizing the technology investigsted: organizing-and-preparing; dericting; modeling; reflecting; creating.